An efficient synthesis of lamellarin alkaloids: Synthesis of lamellarin G trimethyl ether - Somsak Ruchirawat (2018)
A general and efficient synthesis of lamellarin alkaloids is described. The synthesis involves the formation of the core pyrrolo[2,1-a]isoquinoline, followed by the formation of the lactone ring. © 2001 Published by Elsevier Science Ltd.